Case Report: Bloodstream infection with Nocardia cyriacigeorgica in a patient with diffuse large B-cell lymphoma - Du, Ning; Xu, Bingqing; Wang, Hongmin; Tang, Haochun; Li, Jianping; Meng, Jun; You, Dan (Frontiers in Medicine, 2025)
Nocardia bacteremia is a rare but life-threatening opportunistic infection associated with high mortality rates. Early diagnosis and prompt initiation of appropriate treatment are crucial for improving patient outcomes. In our study, we report a patient with diffuse large B-cell lymhoma who unfortunately had a bloodstream infection with Nocardia cyriacigeorgica. The patient presented with characteristic clinical manifestations of septic shock, including persistent high-grade fever, hypotension, and acute renal insufficiency. Despite receiving empirical treatment with imipenem for 6 days following admission, the patient remained febrile with temperatures reaching 39°C. Subsequent blood cultures identified N. cyriacigeorgica, prompting a modification of the antimicrobial regimen to a triple-drug combination of imipenem, linezolid, and trimethoprim-sulfamethoxazole (TMP-SMX). Following the initiation of therapy, the patient demonstrated significant clinical improvement and was subsequently discharged. Based on this clinical experience and the severity of nocardial infections, we recommend combination therapy with two to three antimicrobial agents for the management of Nocardia infections.